2011
DOI: 10.1038/emboj.2011.302
|View full text |Cite
|
Sign up to set email alerts
|

iASPP/p63 autoregulatory feedback loop is required for the homeostasis of stratified epithelia

Abstract: iASPP, an inhibitory member of the ASPP (apoptosis stimulating protein of p53) family, is an evolutionarily conserved inhibitor of p53 which is frequently upregulated in human cancers. However, little is known about the role of iASPP under physiological conditions. Here, we report that iASPP is a critical regulator of epithelial development. We demonstrate a novel autoregulatory feedback loop which controls crucial physiological activities by linking iASPP to p63, via two previously unreported microRNAs, miR-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 55 publications
6
75
0
1
Order By: Relevance
“…7E) explores the contribution of iASPP to the apoptotic cell death response. We have recently shown that iASPP is involved in the maintenance of epidermal homeostasis, regulating genes that are essential for the cell adhesion, differentiation and proliferation of stratified epithelia (Chikh et al, 2011). Here, we have reinforced the notion of a constitutive anti-apoptotic function of iASPP, the expression of which is sufficient to repress apoptosis.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…7E) explores the contribution of iASPP to the apoptotic cell death response. We have recently shown that iASPP is involved in the maintenance of epidermal homeostasis, regulating genes that are essential for the cell adhesion, differentiation and proliferation of stratified epithelia (Chikh et al, 2011). Here, we have reinforced the notion of a constitutive anti-apoptotic function of iASPP, the expression of which is sufficient to repress apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…1A). To understand the molecular mechanisms underlying the resistance to apoptosis demonstrated by iASPPdepleted keratinocytes, we evaluated the expression levels of PMAIP1, the gene encoding Noxa, which we found to be downregulated in our previously published microarray analysis of iASPP-depleted cells (Chikh et al, 2011) (Fig. 1B).…”
Section: Results Iaspp Depletion Protects Cells From Apoptosis By Modmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, p63 directly inhibits expression of miR-138, miR-181a/b, and miR130b in primary human keratinocytes (Rivetti di Val Cervo et al 2012). In turn, p63 expression in epidermal keratinocytes is regulated by miR-203, miR-720, and miR-574-3p, which are expressed in cells within the suprabasal epidermal layer and restrict p63 expression to basal cells (Yi et al 2008;Chikh et al 2011). In addition to the hair bulb, epidermal progenitors generate the sebaceous gland, which secretes sebum via the duct penetrating the upper part of the follicular epithelium and extrudes it into the hair follicle infundibulum (Niemann and Horsley 2012).…”
Section: Va Botchkarev and Er Floresmentioning
confidence: 99%